The Tax Policy and Macro Management: Evidence in Vietnam - D. V. Dinh; N. T. Ha (Финансы: теория и практика, 2023)
The relevance of the study is determined by the need to improve the tax policy of Vietnam.The scientific novelty of the study lies in the application of a regression model for analysing GDP dynamics to determine the optimal tax policy.The purpose of this study is to study the relationship between the tax-to-GDP ratio and economic growth, the optimal threshold for the tax-toGDP ratio, and to compare empirical results with actual tax-to-GDP ratios as a basis for improving tax policy and government micromanagement.The methodology of this study includes a threshold regression model, a unit root test, and a cointegration test to examine the impact of the ratio of tax revenues to GDP-on-GDP growth. The author used actual data on the dynamics of tax revenues and GDP over a 25-year period: from 1994 to 2020, reflected the development of economic growth studies.It is shown that the ratio of tax revenues to GDP and GDP growth are closely related at the level of 86%. The relationship between Vietnam’s tax policy and economic growth is long-term, and the optimal threshold for the ratio of tax revenue to GDP is 19%, which leads to economic growth. It is concluded that the government should make more efforts to improve fiscal policy and macro management to stimulate economic growth and reduce the budget deficit. Fiscal policy has a significant impact on business entities, that is, economic organizations that create wealth for society and high employment, which leads to a decrease in unemployment. The results of the study can be used to form the tax policy of Vietnam.